Playing sociology: theory and games for coping with mimetic crisis and social conflict - Doni, Martino (Studies in violence, mimesis, and culture, 2024)
"This book speaks of the social sciences and play not as two separate realities but as one intertwined experience: to study human behavior is already to put oneself in the game; it is already part of a great game that humanity have never fully learned. Play is not just an object of study but is also practice and method; in the second part, the authors present five sociological games that can be used as research tools and as training models for schools, companies, and work groups"--